Early ID Outpatient Follow-up of OPAT Patients Reduces 30-day Readmission. (4th October 2017) - Saini, Ena; Ali, Mohammad; Du, Ping; Crook, Tonya; Zurlo, John
Abstract: Background: Although weekly outpatient follow-up for patients discharged on outpatient parenteral antimicrobial therapy (OPAT) has been recommended, few practitioners follow this recommendation. No studies have examined the relationship between outpatient follow-up and patient outcomes for this population. We examined the association between outpatient ID follow-up and the risk for 30-day readmission for patients discharged on OPAT. Methods: We conducted a retrospective cohort study using EMR data comprising 1102 OPAT patients treated between January 2012 and December 2014 at a major tertiary care medical center. We sought to determine whether ID outpatient follow-up was associated with a lower risk of 30-day readmission, after adjusting for patient demographics, infection diagnosis, outpatient antibiotics, and comorbidities (mainly diabetes mellitus, renal failure and immunosuppression). Results: Of 1102 cases, 201 of 1102 (18%, 95 females, 106 males) were readmitted within 30 days, of whom 133 (66%) were re-admitted in the first 2 weeks post discharge. 837 (76%) were seen in ID outpatient follow-up within 30 days of discharge, of whom 396 (47%) were seen in first 2 weeks. By univariate analysis OPAT patients seen in ID outpatient follow-up within 2 weeks of discharge were less likely to get readmitted within 30 days of hospital discharge (OR: 0.6, CI: 0.4–0.9, P < 0.02). Patients with immunosuppression (OR: 1.9, 95% CI: 1.3–2.7, P < 0.0001) or discharged on 3 or more antimicrobials (OR: 2.1, 95% CI:1.4–3.2, P < 0.0001) were more likely to have 30-day readmission. By multivariate analysis patients seen in outpatient ID follow-up within 2 weeks (OR: 0.6, CI: 0.4–0.9, P < 0.006) or those receiving ceftriaxone alone (OR: 0.6, CI: 0.3–0.9, P < 0.015) were less likely to have 30-day readmission. Patients who were immunosuppressed (OR: 1.9, CI: 1.3–3.0, P < 0.003) or those discharged on 3 or more antimicrobials (OR: 2.1, CI: 1.4–3.2, P < 0.001) were more likely to have 30-day readmission. Conclusion: Infectious disease outpatient follow-up within 2 weeks for patients discharged on OPAT reduces all-cause 30-day readmission. Early outpatient follow-up is especially important for patients who are immunosuppressed and those receiving multiple antibiotics. Disclosures: All authors: No reported disclosures.